2020
DOI: 10.3390/ijms21031080
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Genes at Panicle Initiation and Grain Filling Stages Implied in Heterosis of Rice Hybrids

Abstract: RNA-Seq technology was used to analyze the transcriptome of two rice hybrids, Ajay (based on wild-abortive (WA)-cytoplasm) and Rajalaxmi (based on Kalinga-cytoplasm), and their respective parents at the panicle initiation (PI) and grain filling (GF) stages. Around 293 and 302 million high quality paired-end reads of Ajay and Rajalaxmi, respectively, were generated and aligned against the Nipponbare reference genome. Transcriptome profiling of Ajay revealed 2814 and 4819 differentially expressed genes (DEGs) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…The molecular mechanism of heterosis still remains mysterious despite research on heterosis for more than a century. Unfolding research ndings indicate the potential to improve heterosis by exploiting inter-speci c heterosis between African rice and Asian rice 45 , differential expression of genes 46 , divergent selection and genetic introgression 47 , genomic hybrid breeding using whole genome markers 48 , epistasis interactions between select parents 49 , chromosome-segment substitution lines 47 , heterotic loci from wild Oryza longistaminata for yield heterosis 50 , wide compatible neo-tetraploid rice line with long panicles 51 and genome wide transcriptome pro ling of O. ru pogon 52 .…”
Section: Unsettled Issuesmentioning
confidence: 99%
“…The molecular mechanism of heterosis still remains mysterious despite research on heterosis for more than a century. Unfolding research ndings indicate the potential to improve heterosis by exploiting inter-speci c heterosis between African rice and Asian rice 45 , differential expression of genes 46 , divergent selection and genetic introgression 47 , genomic hybrid breeding using whole genome markers 48 , epistasis interactions between select parents 49 , chromosome-segment substitution lines 47 , heterotic loci from wild Oryza longistaminata for yield heterosis 50 , wide compatible neo-tetraploid rice line with long panicles 51 and genome wide transcriptome pro ling of O. ru pogon 52 .…”
Section: Unsettled Issuesmentioning
confidence: 99%
“…In particular, the gene expression patterns involved in some metabolic pathways are obviously correlated with heterotic phenotypes. For example, several studies on heterosis in rice revealed that differentially expressed genes between hybrids and their parents were involved in energy metabolism, which contributed in a significant way to the increased yield of hybrids [ 11 , 12 ]. Fujimoto et al [ 13 ] demonstrated that the higher photosynthetic efficiency of Arabidopsis hybrids was obviously associated with the early increase in the activity of genes involved in chlorophyll biosynthesis and photosynthesis, which contributed to increased heterotic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, many transcriptome studies have provided insights into the molecular basis of heterosis in different species, such as rice [ 8 , 12 ], Arabidopsis [ 13 , 14 ] and maize [ 15 , 16 ]. In these studies, an extremely high number of differentially expressed genes (DEGs) associated with different biochemical pathways have been found to be related to heterosis.…”
Section: Introductionmentioning
confidence: 99%